2022
DOI: 10.3389/fpls.2022.963873
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ZmIPT2 gene delays leaf senescence and improves grain yield in maize

Abstract: Cytokinins (CTKs) are a major phytohormone group that are significant in the promotion of cellular division, growth, and divergence. Isopentenyl transferase (IPT) regulates a rate-limiting step in plant CTK synthesis, promotes the synthesis of isopentenyl adenonucleotides from 5-AMP and isopentenyl pyrophosphate, and then converts both these chemicals into various CTKs. Here, the full-length cDNA of ZmIPT2, which encodes 322 amino acids, was isolated and was introduced into a maize inbred line by Agrobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…Phytohormones are small molecules that modulate diverse physiological and cellular responses and play crucial roles in mediating Chl accumulation [ 70 , 71 ]. Extensive investigations have revealed the positive roles of IAA, CTK, GA, and SA [ 72 75 ], and the negative roles of ETH, JA, and ABA in Chl accumulation [ 76 78 ]. However, Previous studies reported a marked decline in the Chl content in oil palm [ 79 ] and Arabidopsis [ 80 ] following GA 3 and IAA treatments, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones are small molecules that modulate diverse physiological and cellular responses and play crucial roles in mediating Chl accumulation [ 70 , 71 ]. Extensive investigations have revealed the positive roles of IAA, CTK, GA, and SA [ 72 75 ], and the negative roles of ETH, JA, and ABA in Chl accumulation [ 76 78 ]. However, Previous studies reported a marked decline in the Chl content in oil palm [ 79 ] and Arabidopsis [ 80 ] following GA 3 and IAA treatments, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Zm00001d011673, which is also named fps2 , encodes the farnesyl diphosphate synthase 2 protein. A previous study showed that Zm00001d011673 can interact with ZmIPT2, which can regulate leaf senescence and grain yield in maize ( Song et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll content is an indicator of photosynthesis activity, which can directly affect photosynthetic efficiency [44][45][46]. A large number of functional genes related to chlorophyll have been identified by analysis of many mutants in maize, rice, and other species [47][48][49]. However, chlorophyll content is a quantitative trait controlled by multiple genes, which requires further study on its function.…”
Section: Discussionmentioning
confidence: 99%